CONTROL OVER PROCESS OF SIMULTANEOUS DOUBLE-SIDED LENS FORMATION AT PRELIMINARY PROCESSING STAGE - I. P. Filonov; A. S. Kozeruk; E. O. Lapteva; M. I. Filonova; V. O. Kuznechik; A. V. Vasilevich (Наука и техника)
Methodology for determination of optimum setting parameters for technological equipment that ensure the prescribed accuracy of a work-piece at the preliminary machining stage under conditions of free rubbing has been developed in the paper. The paper describes a scheme for dividing lens surface into elementary sites. The so called reference points are accepted in the centre of the sites and ways of their friction are calculated which are directly-proportional connected with intensity of metal envelope removal under machining conditions using free rubbing method. Methodology for determination of range in length change of line mark during tool oscillatory motion has been proposed and analytical expressions for calculation of this range for every specific case have been obtained in the paper. The paper contains calculation of friction ways in reference points of lens diametrical cross-section for various combinations of such setting parameters of technological equipment to ensure simultaneous lens processing as length of mark line during tool oscillatory motion, rotation frequency of a lens and an input element in an executing mechanism of a machine tool, tool diameter and ratio of its frequency rotation to lens frequency rotation.The paper shows that if control over the shaping process is executed through regulation of rotation frequency of the lens and the input element in the machine tool executing mechanism then unacceptable accuracy of the machined surface is obtained in case of their equal values. The highest accuracy of the machined surface can be reached while regulating ratio value of tool and lens rotation in combination with the change of tool diameter. Experimental investigations on polishing of lens convex surface have been carried out and they correlate with theoretical calculations. Such method of investigations as a mathematical simulation of technological equipment operational zone for processing highly-accurate spherical surfaces under conditions of free rubbing has been used in the paper.